Penyembunyian Aset dalam Pencucian Uang: Modus Baru dan Implikasi bagi Penegakan Hukum - Arifin, Muhammad Zainul; Mutmainnah, Ummu Kaidah; Pratama, Muhammad Farhan; Sapitri, Wahyuni; Ramadhan, Muhammad Syahri (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
Indonesia was ranked 61 out of 164 countries (6.32 out of 10) based on the Basel AML Index in 2024. The Basel AML Index score reflects a country's vulnerability to money laundering and terrorist financing. Although not among the countries with the highest risk globally, this score indicates that Indonesia still has work to do to improve the effectiveness of its AML/CFT/CPF framework. Moreover, the newly emerging money laundering schemes, one of which involves untraceable assets like cryptocurrency, make it more difficult to carry out legal proceedings. The novelty in this study is the discovery of assets disguised in money laundering, which is expected to ease the Financial Transaction Reporting and Analysis Center (Pusat Pelaporan dan Analisis Transaksi Keuangan-PPATK) to track hard-to-trace assets. This study was conducted using a juridical-normative method. The result showed various methods in money laundering activities, namely transferring and/or investing funds obtained from illicit activities, corruption, bribery, fraud, irregularities through the banking sector, capital markets, and other means such as deposits, stocks, bonds, and various financial instruments. The various modus operandi carried out by corrupt individuals in money laundering in various sectors require more attention from PPATK.